Race, ethnicity, and telecommunications policy issues of access and representation: Centering communities of color and their concerns. (June 2019) - Moran, Rachel E.; Bui, Matthew N.
Abstract: This paper examines how and why activist groups representing marginalized communities of color are increasingly engaging in communications technology policy issues, particularly in relation to issues of digital access and representation. It explores three distinct but related case studies to disentangle the issues and concerns of a range of communities of color, and the challenges and opportunities for their advocates in navigating the highly technical communications technology policy arena: the first case study, which centers on the NAACP's original opposition to net neutrality, reveals the primacy of issues surrounding the "digital divide" to populations of color, and the difficulties of engaging in technical conversations surrounding Internet governance when issues of access persist. Meanwhile, the second case reviews the campaign by Free Press to promote set-top box liberalization as an issue of representation and diversity to both policymakers and citizens. The final case, which examines the work of the Tribal International Carrier to build an alternative internet service network for Native populations, highlights the precarity which organizations must strategically navigate in order to mitigate the influence of both the state and large corporations over Internet policy issues in order to both serve and represent their constituents. In all, this paper presents and extends upon a novel approach to communications policy research, foregrounding the need to integrate critical race frameworks and, relatedly, to center the breadth, depth, and lived experiences of communities of color, which can therein facilitate more inclusive digital media and communication environments and policy structures. Highlights: Communities of color, are increasingly involved in telecommunications policy debates. The first-level digital divide disproportionately affects communities of color. Communities of color are not monolithic in their motivations, resources and positions in telecommunications policy. Critical Race Theory is an important lens for policy discussion to include communities of color.